Hubungan Durasi Penggunaan Media Sosial dengan Kualitas Tidur Pada Remaja di SLB Negeri 2 Yogyakarta - Tiara Aghivana Pratiwi; Sujono Riyadi (Jurnal Indonesia Sehat, 2023)
Background: Good quality sleep will result in freshness and well- being whenawakened. Adolescents with poor sleep quality can be due to various reasons, one of which is the use of social media. Purpose: To find out the relationship between the duration of social media use and sleep quality at SLB Ngeri 2 Yogyakarta. Methods: This study used a cross sectional approach. The sampling technique used in this study was purposive sampling with a sample size of 35 teenagers at SLB Negeri 2 Yogyakarta. The questionnaire used in this study was the Social Media Questionnaire and the Pittsburgh Sleep Quality Index (PSQI) for sleep quality. Data analysis used the Somers' d Correlation test. Results: There is a significant relationship between the duration of social media use and the sleep quality of adolescents at SLB Negeri 2 Yogyakarta as shown in Table 4.5. The p- value is 0.002 and the somers'd correlation value is 0.471 which is a lower value than the significant level (p?0.05), indicating that the duration of using social media Facebook, Instagram and WhatsApp is in the moderate category and experiencing poor sleep quality in 29 respondents (100.0%). Conclusion: Teenagers are required to reduce the use of social media in their daily activities, especially at night so as to produce good quality sleep.